Safari, so good! all about African wildlife - Worth, Bonnie; Mathieu, Joe; Ruiz, Aristides (London A Random House Group Cpmpany, 2011)
Take a walk on the wild side with the Cat in the Hat! Meet all the animals, big and small, that make safari, so good! Spot cats, elephants, zebra, giraffe, hippos, warthogs, buffalo, baboons, side-striped jackals, spotted hyena, pythons, vipers, and six kinds of antelope!
"I'm Ready for reading"
English stories
2
Keywords: English stories